The Study on the Structure of NdFe1−xCoxO3, the Analysis of Mössbauer Spectra, and the Discussion of Its Constituent Elements. Issue 2 (31st October 2022) - Gao, Kaiyang; Shen, Jiyu; Mo, Jiajun; Li, Hao; Jia, Zihan; Li, Zimeng; Yang, Dingguo; Liu, Min; Xia, Yanfang
Abstract : NdFe1− x Co x O3 samples are prepared by the sol–gel method. The X‐ray diffraction (XRD) results show that these samples conform to the orthogonal perovskite structure (Pbnm), and different doping amounts can cause the patterns to shift by XRD pattern. Through the Williamson–Hall analysis, the microstrain of the lattice between different doping amounts was obtained, and the average crystal size was calculated. The element content of each sample was obtained by scanning electron microscope and energy‐dispersive X‐ray analysis. Mössbauer spectra show that different doping levels change the surrounding environment of iron, and the magnetic properties of the samples also change. Abstract : Herein, the NdFe1− x Co x O3 samples are tested by X‐ray diffraction, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, and Mössbauer spectra and combined with studying the material's conductivity. The influence of Co doping on the internal production of perovskite and its causes are revealed. At the same time, this article may be the first to test the Mössbauer spectra of NdFe1− x Co x O3 at room temperature (300 K).